2007
DOI: 10.1158/1055-9965.epi-07-0368
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Isoflavones and Fibrocystic Breast Conditions and Breast Cancer Among Women in Shanghai, China

Abstract: Background: Proliferative benign breast conditions are associated with elevated risk of breast cancer, whereas nonproliferative conditions are not strongly associated with risk. Factors acting before onset of hyperplasia might be associated with both benign conditions and breast cancer, whereas those on the proliferative disease-tocancer pathway would be associated only with cancer. Soy isoflavone exposure may influence breast cancer risk, but little is known of its association with benign conditions. Material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 30 publications
2
30
0
1
Order By: Relevance
“…To minimize the attenuation of risk estimates derived from random measurement errors, the authors matched fasting time between cases and controls [37]. In addition, another recently published Chinese case-control study showed a significant breast cancer risk reduction in women with high plasma levels of genistein (OR 0.26, 95% CI 0.13-0.50) [38].…”
Section: High Isoflavone Consumption and Breast Cancer Riskmentioning
confidence: 99%
“…To minimize the attenuation of risk estimates derived from random measurement errors, the authors matched fasting time between cases and controls [37]. In addition, another recently published Chinese case-control study showed a significant breast cancer risk reduction in women with high plasma levels of genistein (OR 0.26, 95% CI 0.13-0.50) [38].…”
Section: High Isoflavone Consumption and Breast Cancer Riskmentioning
confidence: 99%
“…Genistein (4,5,7-trihydroxyisoflavone) has been identified as the predominant isoflavone in soybean enriched foods which comprises a significant portion of the Asian diet, and provides 10% of the total per capita protein intake in Japan and China. A recent study among women in Shanghai, China found that plasma isoflavone concentration were inversely associated with the risk of non-proliferative and proliferative benign fibrocystic conditions as well as breast cancer [1]. In parallel, relatively high levels of soy isoflavones have been found in the serum, urine and prostatic fluid of Asian men who consume a soy rich diet possibly contributing in lowering the incidence of prostate cancer [2;3].…”
Section: Introductionmentioning
confidence: 99%
“…Strikingly, a randomized, double-blinded, placebo-controlled study of 383 women indicated that the magnitude of the protective association was similar in western populations despite their markedly different levels of intake compared to Asian women [25]. Intake of genistein may protect against the development of breast and prostate cancer and did not cause the development of new, estrogen-dependent breast or reproductive tissue cancers [20, 26]. In addition to its chemoprevention effect on breast and prostate cancer, genistein can be selectively cytotoxic to neoplastic and preneoplastic cells as well as lung and pancreatic cancer cell lines in vitro [2729].…”
Section: Introductionmentioning
confidence: 99%